The multifunctional role of filaggrin in allergic skin disease. - Irvine, Alan; McAleer, Maeve (My University, 2013)
Filaggrin is a major structural protein in the stratum corneum of the epidermis. Mutations in the filaggrin gene are the most significant known genetic risk factor for the development of atopic dermatitis. Mutations in the human filaggrin gene (FLG) also confer risk for the associated allergic diseases of food allergy, asthma, and allergic rhinitis. These discoveries have highlighted the importance of skin barrier function in the pathogenesis of atopic diseases and have motivated a surge in research characterizing the filaggrin-deficient skin barrier and its consequences. In this review we discuss the mechanisms through which mutations in this protein contribute to the pathogenesis of atopic dermatitis and associated atopic conditions. We focus on recent human and murine discoveries characterizing the filaggrin-deficient epidermis with respect to biophysical, immunologic, and microbiome abnormalities.
PUBLISHED
Keywords: Filaggrin; Immunology, Inflammation & Infection